Study of Changes in Cholesterol 7 Alpha Hydroxylase in Patients with Gall Stone in Babylon Province (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
The gallbladder (GB) is an assistant organ of the digestive system, It is  located under the liver and attached to the biliary system, And it is responsible for controlling release of bile and the storage. Gallstone disease a major health problem worldwide. In 10–15% of adults contain gallstone disease. This study (case control) consists of  one hundred sixty (160) patients are included in this study randomly selected  and consisted of 130 females and 30 males. All patients are examined 24 hr. Before operation, Intra operatively and 24hr post operatively. Decreased gallbladder motility and the decrease of cholesterol 7 –alpha hydroxylase activity, which regulate the novo bile salt synthesis. The rate-limiting step of bile acid synthesis is acting between the liver-specific CYP 7A1 (CYP450). Thus, Alteration in CYP gene control also has an impact on bile acid synthesis and lipid metabolism.